Rub out the words : letters 1959 - 1974 - Burroughs, William S., 1914-1997; Morgan, Bill, 1949- (London : Penguin Books, 2013)
Briefwisseling van Williams S. Burroughs, mede-oprichter van de beatnik-generatie.
Includes bibliographical references and index
Originally published: New York: Ecco; London: Penguin Classics, 2012
Keywords: Burroughs, William S, -- 1914-1997 -- Correspondence; Burroughs, William S., -- 1914-1997.; Ginsberg, Allen, -- 1926-1997 -- Correspondence; Kerouac, Jack, -- 1922-1969 -- Correspondence; Authors, American -- 20th century -- Correspondence